Radical Prostatectomy and Pelvic Lymph Node Dissection in Kaiser Permanente Southern California: 15-Year Experience - Banapour, Pooya (Perm J, 2019)
INTRODUCTION: Radical prostatectomy (RP) with pelvic lymph node dissection (PLND) is the standard treatment of high-risk prostate cancer. High-risk patients and those with lymph node metastasis (LNM) require further treatment. We review outcomes of RP+PLND in Kaiser Permanente Southern California (KPSC). METHODS: Patients who underwent RP+PLND in KPSC from January 1, 2001, to July 1, 2015 were included. Patient charts were retrospectively reviewed for demographic information and clinicopathologic data which were used to calculate positive surgical margin rate, LNM, adjuvant treatment, 5-year biochemical recurrence, and overall survival. Univariate and multivariate logistic regression analyses were used to identify factors associated with margin positivity. RESULTS: Patients (N = 1829) underwent RP+PLND (241 high-risk, 943 intermediate-risk, 645 low-risk). Positive margin rates were 17.8%, 14.8%, and 11.9% in the high, intermediate- and low-risk groups. Biochemical recurrence rates were 22% in high-risk and 12.1% in the low-risk category. Androgen deprivation use was 4.1% in the high-risk group and 0.9% in the low-risk group. Five-year overall survival was 92.5% in lymph node-positive patients and 94.9% in lymph node-negative patients (p = 0.8). On multivariate analysis, age (odds ratio [OR] = 1.02, p = 0.02), prebiopsy prostate-specific antigen (OR = 1.02, p < 0.001), and clinical T stage (OR = 1.49, p = 0.01) were associated with margin positivity. CONCLUSION: In KPSC, RP+PLND was performed in patients with low-, intermediate-, and high-risk prostate cancer. Age, prebiopsy prostate-specific antigen, and clinical stage were associated with positive surgical margins in patients with LNM. Recipients of RP+PLND with LNM and positive surgical margins required adjuvant treatment.